Application of Moringa oleifera for development of Sustainable and Biosecure Aquaculture - T. Kamble, Manoj; R. Chavan, Balu; Gabriel, Ataguba; Azpeitia, Txomin (Indonesian Aquaculture Society (MAI), 2014)
As the global scenario is now changing towards the development of sustainable and biosecure aquaculture by using of safe and eco-friendly products. This paper reviews the application of Moringa plant for development of sustainable aquaculture. The Moringa plant shows many applications in aquaculture such as antimicrobial activity, antibacterial efficacy, larvicidal activity, piscicide, anti-cyanobacterial activity, antifertility effect, food supplement and seafood preservative. The use of Moringa as antimicrobial activity of the seed coat and pod husks; as a medicinal plant for protection of Penaeus indicus from pathogenic Vibrio harveyi; as an evidence for cyanobactericidal activity of filtrate from crushed Moringa seeds and isolation of a protease inhibitor. In conclusion, these results suggest that Moringa oleifera showed potentially valuable plant for development of sustainable aquaculture